2017
DOI: 10.17221/50/2016-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Lower nitrogen nutrition determines higher phenolic content of organic apples Juozas Lanauskas1, Darius Kviklys1, Mindaugas Liaudanskas2, Valdimaras

Abstract: Lanauskas J., Kviklys D., Liaudanskas M., Janulis V., Uselis N., Viškelis J., Viškelis P. (2017) th leaf were tested. Nitrogen and potassium fertilizers were applied annually at the rates of 50 kg/ha N and 66.4 kg/ha K in an integrated fruit orchard. A mixture of perennial grasses with 25% of white clover was sown in interrows in the second year after tree establishment in the organic production system. Every two years sward in alternate interrows was tilled for natural organic matter mineralization. Fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Many technological, biological and environmental factors affect apple fruit quality. Our previous studies demonstrated the significant impact of rootstock [1], planting distances [2], tree crown management and tree growth control [3,4], fertilization [5], crop load management [6], orchard location [7], etc., on external and internal fruit quality parameters. Most of these practices could be attributed to the improvement of light conditions and to the increase of light interception in modern orchards.…”
Section: Introductionmentioning
confidence: 99%
“…Many technological, biological and environmental factors affect apple fruit quality. Our previous studies demonstrated the significant impact of rootstock [1], planting distances [2], tree crown management and tree growth control [3,4], fertilization [5], crop load management [6], orchard location [7], etc., on external and internal fruit quality parameters. Most of these practices could be attributed to the improvement of light conditions and to the increase of light interception in modern orchards.…”
Section: Introductionmentioning
confidence: 99%